Clinical outcomes of sorafenib treatment failure for advanced hepatocellular carcinoma and candidates for regorafenib treatment in real‐world practice. Issue 10 (27th May 2018) - Uchikawa, Shinsuke; Kawaoka, Tomokazu; Aikata, Hiroshi; Kodama, Kenichiro; Nishida, Yuno; Inagaki, Yuki; Hatooka, Masahiro; Morio, Kei; Nakahara, Takashi; Murakami, Eisuke; Hiramatsu, Akira; Tsuge, Masataka; et al.
Abstract : Aim: As second‐line therapy, regorafenib has been shown to provide a survival benefit for patients with hepatocellular carcinoma (HCC) who progress on sorafenib. In this retrospective study, we assessed the clinical outcomes of sorafenib treatment failure with regard to second‐line chemotherapy. Methods: Patients ( n  = 160) with advanced HCC, Child–Pugh A liver function and Eastern Cooperative Oncology Group performance status (ECOG PS) 0–1 treated with sorafenib between June 2009 and September 2016 were enrolled. Among 147 patients with progressive disease (PD), we defined those with Child–Pugh A liver function and ECOG PS 0–1 at progression as candidates for second‐line chemotherapy and those who had tolerated sorafenib (≥400 mg/day for ≥20 of the last 28 days of treatment) as candidates eligible for regorafenib treatment. Results: Among all 160 patients, median overall survival was 10 months, and median progression‐free survival was 3.5 months. Among the 147 patients with PD, 74 (50.3%) were candidates for second‐line chemotherapy, and 45 (30.6%) were eligible for regorafenib treatment. The median post progression survival of the candidates for second‐line chemotherapy (8.8 months) was statistically longer ( P  = 0.0002) than that of the non‐candidates (3.6 months). Predictive factors for candidates were absence of macroscopic vascular invasion (MVI) (odds ratio [OR], 0.39; P  = 0.009) and serum albumin >3.5 g/dL (OR, 3.3; P  = 0.005) at sorafenib initiation. Conclusion: Among patients with PD on sorafenib, approximately 30% were eligible for regorafenib treatment, whereas few patients with MVI or hypoalbuminemia at sorafenib initiation were eligible for regorafenib treatment.